A Metal–Organic Framework with a Pore Size/Shape Suitable for Strong Binding and Close Packing of Methane. Issue 15 (7th March 2016) - Lin, Jiao‐Min; He, Chun‐Ting; Liu, Yan; Liao, Pei‐Qin; Zhou, Dong‐Dong; Zhang, Jie‐Peng; Chen, Xiao‐Ming
Abstract: Much effort has been devoted to develop new porous structures for methane storage. We report a new porous coordination framework showing exceptional methane uptakes (e.g. 263 v / v at 298 K and 65 bar) and adsorption enthalpies (21.6 kJ mol −1 ) as high as current record holders functionalized by open metal sites. Computational simulations demonstrated that the hierarchical pore structure consisting of single‐wall nanocages has suitable sizes/shapes and organic binding sites to enforce not only strong host–methane and methane–methane interactions but also dense packing of methane molecules. Abstract : Hold tightly : High‐density methane storage is achieved in a metal–organic framework featuring a hierarchical pore system consisting of single‐wall nanocages and strong organic binding sites. These enforce not only strong host–methane and methane–methane interactions, but also a dense packing of methane molecules.